2010
DOI: 10.1007/s11274-010-0573-6
|View full text |Cite
|
Sign up to set email alerts
|

Nitrite effect on ammonium and nitrite oxidizing processes in a nitrifying sludge

Abstract: Nitrite accumulation can be undesirable in nitrifying reactors used for the biological elimination of nitrogen from wastewaters because the ammonium oxidation process was seen to be inhibited. There is a need to better understand the effects of nitrite on both ammonium and nitrite oxidizing processes. In this paper, the effect of nitrite on the nitrifying activity of a sludge produced in steady-state nitrification was evaluated in batch cultures. At 25 mg N/l of added nitrite, nitrification was successfully ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
0
8
0
1
Order By: Relevance
“…Toxicity from phosphorusprecipitation spectator ions, heavy metals, and cyanide against anammox was reported. Silva et al (2011a) studied the effect of nitrite on batch sludge cultures. High nitrite concentrations inhibited nitrite-oxidizing processes more than ammonium-oxidizing processes.…”
Section: Reactor Inhibition/optimizationmentioning
confidence: 99%
“…Toxicity from phosphorusprecipitation spectator ions, heavy metals, and cyanide against anammox was reported. Silva et al (2011a) studied the effect of nitrite on batch sludge cultures. High nitrite concentrations inhibited nitrite-oxidizing processes more than ammonium-oxidizing processes.…”
Section: Reactor Inhibition/optimizationmentioning
confidence: 99%
“…Nitrous acid is known to inhibit nitrification, thus, low pH values must be avoided in nitrifying processes (Anthonisen et al, 1976;Vadivelu et al, 2006aVadivelu et al, , 2006b. Recently, Silva et al (2011) reported that the nitrite-oxidizing process was more sensitive to the presence of nitrite than the ammonium-oxidizing process, suggesting that nitrite accumulation in nitrification systems should be controlled to avoid a higher accumulation of nitrite and a decrease in nitrate yield. In consequence, pH value is generally controlled in nitrifying systems and maintained between 7.5 and 8.0 to avoid operational problems.…”
Section: Environmental Factors Affecting Nitrificationmentioning
confidence: 99%
“…In the last decades, several nitrifying consortia have been reported to oxidize simultaneously ammonium and various recalcitrant aromatic compounds, such as phenolic compounds (phenol, 2-chlorophenol, p-cresol, p-hydroxybenzaldehyde) (Amor et al, 2005;Martínez-Hernández et al, 2011;Silva et al, 2009Silva et al, , 2011Vázquez et al, 2006;Yamaghisi et al, 2001) and BTX compounds (Zepeda et al, 2003(Zepeda et al, , 2006(Zepeda et al, , 2007. In some cases, nitrate and carbon dioxide were the major products from the process.…”
Section: Simultaneous Elimination Of Ammonium Organic Matter and Btxmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, NO 2 -is scarcely observed in the natural environment because nitrite oxidizers, such as Nitrobacter and Nitrospira, oxidize NO 2 -to NO 3 -immediately. However, it is also a fact that NO 2 -accumulation is observed under several environmental conditions (Burns et al 1996;Corriveau et al 2010;Silva et al 2011). In swine manure composting, notable N 2 O emission begins after the thermophilic phase, because nitrifying bacteria cannot be active under thermophilic conditions, such as high temperature, high free ammonia and high organic matter content.…”
Section: Effect Of Nitrite Accumulation On N 2 O Emissionmentioning
confidence: 99%